Open circuit potentiometry reports on internal redox states of cells in G. Sulfurreducens biofilms - Schrott, Germán David (2019)
The outstanding capacity of Geobacter sulfurreducens cells to directly connect their inner electron transport chain to a polarized electrode have prompted the application of a wide arrange of electrochemical techniques to explore their metabolism and current production possibilities. In this work we use very basic electrochemical assays as open circuit potential, voltammetric and chronopotentiometric measurements to obtain fundamental information on bacterial electrochemical characteristics of importance to interpret bacterial functioning. Specifically, we obtained information on G. sulfurreducens biofilm capacity to store charge in three major molecular reservoirs bridging the gap between NADH and the electrode, demonstrating, at the same time, the value of OCP measurements as a reporter of internal redox state of cells.